2023
DOI: 10.1088/1361-6668/acdbed
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nanoscale chemistry of as-received and fast neutron irradiated Nb3Sn RRP® wires using atom probe tomography

Abstract: Atom Probe Tomography has been used to study the effect of fast neutron irradiation on the local chemistry of Nb3Sn samples. Two RRP® wires doped with 2 at% Ti were analysed, one in the as-received condition and the other irradiated to a neutron fluence (E>0.1MeV) of 2.82x1022 m-2 in the TRIGA-II reactor. The irradiated sample had a reduced Tc, an increase in Fp, a shift in the peak of the Fp curve suggesting the introduction of secondary point pinning, and an increase in the estimated scaling field B*. Ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Dew-Hughes [36] calculated theoretical characteristic values for p and q for different pinning mechanisms, in particularly for point defect (PD) and grain boundary (GB) pinning. The evolution of the dominant pinning mechanism from GB-to PD-pinning in Nb3Sn under neutron irradiation was recently reported by Wheatley et al [39], who showed that the unirradiated Nb3Sn alloy exhibits |𝐹 𝑝 ⃗⃗⃗ (𝐵, 𝑇)| form indicating the dominance of the GB-pinning, and after the neutron irradiation the |𝐹 𝑝 ⃗⃗⃗ (𝐵, 𝑇)| form transforms towards the PD-pinning mode.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Dew-Hughes [36] calculated theoretical characteristic values for p and q for different pinning mechanisms, in particularly for point defect (PD) and grain boundary (GB) pinning. The evolution of the dominant pinning mechanism from GB-to PD-pinning in Nb3Sn under neutron irradiation was recently reported by Wheatley et al [39], who showed that the unirradiated Nb3Sn alloy exhibits |𝐹 𝑝 ⃗⃗⃗ (𝐵, 𝑇)| form indicating the dominance of the GB-pinning, and after the neutron irradiation the |𝐹 𝑝 ⃗⃗⃗ (𝐵, 𝑇)| form transforms towards the PD-pinning mode.…”
mentioning
confidence: 58%
“…In this report we re-analysed experimental data on the dependence of the maximum pinning force density, |𝐹 𝑝,𝑚𝑎𝑥 (𝑑, 𝑇 = 4.2 K)| (deduced from the |𝐹 𝑝 (𝐵)| [35][36][37] projection) from the average grain size in practical low-Tc multifilamentary Nb3Sn conductors [38][39][40][41][42][43][44][45][46]55,56,58] fabricated by bronze and power-in-tube technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we reanalyzed experimental data on the dependence of the maximum pinning force density, F p,max , from the average grain size, d, in practical low-T c multifilamentary Nb 3 Sn conductors [38][39][40][41][42][43][44][45][46]55,56,58] fabricated by bronze and power-in-tube technologies.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a continuous function, the experimental measurements of material parameters need to be fitted as a function of Sn content. Following the treatment in [21], we use global fits to the experimental T , c g and r versus b in the entire A15 range (table 1), One can see the fitting curves as figure A1 below. With sufficient data available for the critical temperature T c and the transport scattering resistivity r, we choose cubic fit to achieve an exact representation.…”
Section: Appendix the Dependence Of Materials Parameters With Tin Con...mentioning
confidence: 99%
“…It is assumed that this tin variation is a non-negligible contribution to the disagreement between the scaling laws and the experimental results. To improve the scaling law it is useful to understand how B c2 varies with Sn content (see [21][22][23] for recent advances in composition dependences of superconducting properties), since a Nb 3 Sn conductor has practically tin composition content that covers the full range of A15 phase (generally thought to range from ∼18-25 at.% Sn). Following the approach proposed by the same author [24], we begin with the dependence of GL (Ginzburg-Landau) parameters k on the three independent material parameters that are the transport scattering resistivity r W , m low-temperature coefficient of electronic heat capacity g mJ and transition temperature T c [25].…”
Section: Introductionmentioning
confidence: 99%